2012
DOI: 10.1080/02755947.2012.685142
|View full text |Cite
|
Sign up to set email alerts
|

A Reward‐Recovery Study to Estimate Tagged‐Fish Reporting Rates by Idaho Anglers

Abstract: From 2006 to 2009, we tagged and released 22,202 fish with T‐bar anchor tags valued at US$0 to $200 if returned. Our intent was to assess angler tag reporting rates in Idaho and to determine whether reporting rates declined over time or differed between species. A total of 4,643 tags were reported by anglers. Assuming a reporting rate of 100% for $200 tags, weighted mean reporting rates were 54.2% for $0 tags, 69.7% for $10 tags, 91.7% for $50 tags, and 98.9% for $100 tags. By combining $100 and $200 as high‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…Partnerships have long existed among scientists, nonprofit organizations, and volunteers interested in freshwater ecosystems. For example, for several decades, fisheries biologists have partnered closely with anglers to gain information about the size, age, and location of harvested fishes through tag returns (Cardona-Pons et al 2010, Meyer et al 2012. These data are used by fisheries biologists for developing population estimates (Pine et al 2003), validating ages (Bruch et al 2009), and assessing fish movement patterns (Hilborn 1990).…”
mentioning
confidence: 99%
“…Partnerships have long existed among scientists, nonprofit organizations, and volunteers interested in freshwater ecosystems. For example, for several decades, fisheries biologists have partnered closely with anglers to gain information about the size, age, and location of harvested fishes through tag returns (Cardona-Pons et al 2010, Meyer et al 2012. These data are used by fisheries biologists for developing population estimates (Pine et al 2003), validating ages (Bruch et al 2009), and assessing fish movement patterns (Hilborn 1990).…”
mentioning
confidence: 99%
“…Although this assumption is seldom met in practice, when the reporting rate is known or estimated from an independent study or with high-reward tags (e.g. Pollock et al 1991;Meyer et al 2012), mean catch can be divided by the reporting rate to provide an unbiased estimate of mean catch. However, even with known reporting rates, the assumption that all tags that are removed from released fish are reported must be met to provide unbiased estimates of mean catch using this model.…”
Section: Discussionmentioning
confidence: 99%
“…The first assumption was that all tags are reported. In practice, this assumption can be mitigated for if a reporting rate is known or estimated (Pollock et al 2001(Pollock et al , 2002Meyer et al 2012) but still requires that all fish from which tags are removed are reported. Additionally, the model-derived estimator also has the same assumptions common to most tagging studies, such as no tag loss other than anglers removing tags, tagging does not affect survival or catchability, and complete mixing of tagged fish (Pollock et al 2001).…”
Section: Management Briefmentioning
confidence: 99%
See 1 more Smart Citation
“…For Pacific halibut, extensive mixing suggested by passive integrated transponder (PIT) tagging programs [6] has served to justify coastwide assessment modeling [7] and conventional tagging data have been used to estimate seasonal cross-boundary migration rates [8] that are important to consider when discussing fishery season dates (sensu [9]). However, conventional tag-return data can be biased by varying levels and loci of fishing (tag return) effort (sensu [10]), biased rates of tag detection (sensu [11]) or reporting (sensu [12]), and the rates at which tagged animals mix into the untagged population during the interval between mark and recapture (sensu [13]). Furthermore, mark-recovery methods that produce only endpoint data (i.e., locations at tagging and recapture) are unable to address many of the more complex elements of fish-movement dynamics, such as the timing, frequency, and recurrence of movements.…”
Section: Introductionmentioning
confidence: 99%